Alkynyl trifluoromethyl selenide synthesis via oxidative trifluoromethylselenolation of terminal alkynes. Issue 5 (7th April 2015) - Wang, Yuguang; You, Yi; Weng, Zhiqiang
Abstract : A new and efficient Cu-mediated oxidative trifluoromethylselenolation of terminal alkynes for synthesis of alkynyl trifluoromethyl selenides was developed. Abstract : The synthesis of alkynyl trifluoromethyl selenides by Cu-mediated oxidative trifluoromethylselenolation of terminal alkynes is reported. Treatment of [(bpy)Cu(SeCF3 )]2 with various terminal alkynes in the presence of an oxidant, Dess–Martin periodinane, led to the formation of trifluoromethylselenolated acetylenes bearing sensitive moieties such as alkoxy, halogens, trifluoromethyl, and heterocyclic groups.